Internalization of Appearance Ideals and Not Religiosity Indirectly Impacts the Relationship Between Acculturation and Disordered Eating Risk in South and Southeast Asian Women Living in the United States - Negi, Sonakshi; Benau, Erik M.; Strowger, Megan; Grammer, Anne Claire; Timko, C. Alix (Frontiers in Psychology, 2022)
Objective: Studies that examine disordered eating in samples of Asian individuals living in the United States frequently combine all individuals of Asian descent into a single group, which can obscure important differences between groups and their experiences of acculturation. The goal of the present study was to establish the relation of acculturation, internalization of appearance ideals, and religiosity as predicting body dissatisfaction and disordered eating in women of South and Southeast Asian (SSEA) descent. Method: Women of SSEA descent (N = 112) aged 18-51 years (M = 23.10, SD = 6.4) completed a battery of questionnaires that inquire about these variables. A path analysis was conducted with acculturation serving as the independent (exogenous) variable, religiosity and internalization of the thin ideal as mediators, and body dissatisfaction and disordered eating as dependent (endogenous) variables. Results: Direct paths from acculturation to both body dissatisfaction and disordered eating were not significant. Thin ideal internalization completely accounted for the path from acculturation to both endogenous variables; whereas, religiosity did not significantly account for any indirect effect. Discussion: For SSEA women, internalization of appearance ideals is a potentially greater risk factor for disordered eating than acculturation or religiosity. As this was an atemporal mediation analysis, more work needs to be done exploring predictors of internalization in this population and how that may impact the development of disordered eating.